Symbolic Violence on Women Within Religious Sermons - Ma'mun, Sukron; Zakiyya, Sulung Najmawati; Muhsin, Ilyya (UIN Sunan Kudus, 2025)
Violence against women in public spaces remains prevalent and is at times perpetrated by religious figures, including female preachers. This article investigates how symbolic violence against women is reproduced in sermons delivered by Islamic teachers (ustadz) through mass media platforms such as YouTube, Instagram, and Facebook. The study is based on an analysis of sermons by both male and female ustadz who demonstrate a tendency to reinforce gender-based violence. Data were purposively collected from social media sources, particularly on sermons by Ustadz Khalid Basalamah, Oki Setiana Dewi, and Mamah Dedeh. Employing Pierre Bourdieu’s theoretical concepts of symbolic violence and masculine domination, the analysis explores discourses on household dynamics, including spousal obedience, gendered public and domestic roles, and the contested practice of polygamy. The findings indicate a persistent lack of gender sensitivity in these religious discourses, which contributes to the perpetuation of symbolic violence. This subtle form of violence is normalised through mechanisms such as euphemism and implicit censorship, allowing narratives that undermine women’s rights and potential to gain acceptance. The root of this issue lies in the speakers’ inadequate gender awareness and limited interpretative engagement with religious knowledge.